2021
DOI: 10.1007/s12662-021-00731-9
|View full text |Cite
|
Sign up to set email alerts
|

Why feeling competent matters

Abstract: Physical education is an important setting for the promotion of personal resources of children and adolescents. One of the main personal resources in education in general and physical education in particular is self-efficacy. The current study investigated the association between physical education-related self-efficacy and basic psychological need satisfaction according to Self-Determination Theory in adolescent students. A total of 708 students from grades nine to eleven were surveyed using questionnaires. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The nonsignificant indirect effects of peer support on academic performance may be due to similar conceptualizations as parental support. Because findings support a link between basic need satisfaction and higher ASE (Raven & Pels, 2021; Zhen et al, 2017), future research might benefit from using measurements of social support that more specifically assess students' perception of autonomy, competence, or relatedness support from peers and parents.…”
Section: Discussionmentioning
confidence: 99%
“…The nonsignificant indirect effects of peer support on academic performance may be due to similar conceptualizations as parental support. Because findings support a link between basic need satisfaction and higher ASE (Raven & Pels, 2021; Zhen et al, 2017), future research might benefit from using measurements of social support that more specifically assess students' perception of autonomy, competence, or relatedness support from peers and parents.…”
Section: Discussionmentioning
confidence: 99%
“…But in social cognitive theory, self-efficacy encourages persistence (Rogers et al, 2014). The distinction between competence and self-efficacy is that the need for competence centers on one's desire to be capable and high performing overall, while self-efficacy is an outcome-based, futureoriented focus on ability to successfully perform specific tasks (Raven and Pels, 2021;Ryan, 2024). Having reviewed the theoretical background of self-determination theory and social cognitive theory as they relate to education and student learning, the next section discusses the empirical support for these theories.…”
Section: Comparing Constructs Of Self-e Cacy and Competencementioning
confidence: 99%
“…Another study found that autonomous motivation in prospective 1 st year university students was predictive of academic achievement, but academic self-efficacy was not (Fokkens-Bruinsma et al, 2021). Raven and Pels (2021) found that self-efficacy was significantly and positively associated with satisfaction of BPN and performance. Macakova and Wood (2022) found that satisfaction of BPN of college students was positively and directly related to selfefficacy, and indirectly related to academic achievement via selfefficacy.…”
Section: Self-e Cacy and Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the focus was on affective states, although we also investigated relationships between related states and traits. For example, the feeling of satisfaction with one's competence during a physical-education task might serve as a source of self-efficacy (Raven and Pels, 2021). Similarly, repeated experiences of a certain situational motivation may influence the development of a stable motivational disposition (Dietrich et al, 2015).…”
Section: Introductionmentioning
confidence: 99%